Tumor Targeted Multifunctional Magnetic Nanobubbles for MR/US Dual Imaging and Focused Ultrasound Triggered Drug Delivery - Jin, Zhen; Chang, Jinlong; Dou, Peipei; Jin, Shang; Jiao, Min; Tang, Heyun; Jiang, Wenshuai; Ren, Wu; Zheng, Shaohui (Frontiers in Bioengineering and Biotechnology, 2020)
The development of multifunctional nanoplatform that are safe and have multiple therapeutic functions integrated with dual or multi imaging modality is one of the most urgent medical requirements for active cancer therapy. In our study, we prepared a multifunctional magnetic nanobubbles (MF-MNB) by co-encapsulating superparamagnetic iron oxide nanoparticles (SPIONs) and doxorubicin into polylactideco–glycolide–polyethylene glycol–folate (PLGA-PEG-FA) polymer based nanobubbles for tumor-targeted ultrasound (US)/magnetic resonance (MR) imaging and focused ultrasound (FUS) triggered drug delivery. Hydrophobic SPIONs were successfully embedded into MF-MNBs by a typical double emulsion process. The MF-MNBs were highly dispersed with well-defined spherical morphology and an average diameter of 208.4±12.58 nm. The potential of MF-MNB as a dual-modal contrast agent for US and MR imaging was investigated via in-vitro study and the MF-MNB exhibits promising US/MR contrast ability. Moreover, tumor targeting ability was further enhanced by folate conjugation and assessed through in vitro cell test. Furthermore, focused ultrasound, as a non-invasive and remote control technique, was adopted to trigger the release of doxorubicin from MF-MNB and generate the sonoporation effect to enhance drug release and cellular uptake of MF-MNBs. In addition, the 4T1 cell viability was significantly decreased by FA ligand-receptor mediated targeting and FUS sonication. Hence, we believe that the MF-MNB could be a promising drug nanocarrier for US/MR guided anticancer drug delivery to improve cancer treatment efficacy.